Bonding behavior of hydrophobically modified gelatin films on the intestinal surface. (November 2014) - Yoshizawa, Keiko; Taguchi, Tetsushi
The bonding behavior was determined for hydrophobically modified alkaline-treated gelatin on wet porcine intestinal surfaces. The modified gelatin films were obtained by reacting the amino groups of alkaline-treated gelatin with fatty acid chlorides of different alkyl chain lengths, namely, hexanoyl (Hx: C6 ) chloride, decanoyl (Dec: C10 ) chloride, and stearoyl (Ste: C18 ) chloride. Three kinds of the films were prepared, 32HxAlGltn, 24DecAlGltn, and 26SteAlGltn that had substitution ratios of hydrophobic groups to the amino groups of 32HxAlGltn, 24DecAlGltn, and 26SteAlGltn of 32%, 24%, and 26%, respectively. The 32HxAlGltn film had the strongest bonding to porcine intestinal surfaces. A thick 32HxAlGltn film remained on the intestinal surface even after the bonded film was scraped off for the measurement of bonding strength. In addition, the burst strength increased with an increase in the substitution ratio of the Hx group. Thus, the HxAlGltn film with the higher Hx modification ratio has a potential as a sealant material to prevent agglutination of intestinal surfaces.